First experimental results obtained using the highpower free electron laser at the siberian center for photochemical research - Antokhin, E.A.; Akberdin, R.R.; Arbuzov, V.S.; Bokov, M.A.; Bolotin, V.P.; Burenkov, D.B.; Bushuev, A.A.; Veremeenko, V.F; Vinokurov, N.A.; Vobly, P.D.; Gavrilov, N.G.; Gorniker, E.I; et al. (Вопросы атомной науки и техники, 2004)
The first lasing near the wavelength of 140 µm was achieved in April 2003 using a high-power free electron laser (FEL) constructed at the Siberian Center for Photochemical Research. In this paper we briefly describe the design of the FEL driven by an accelerator–recuperator. Characteristics of the electron beam and terahertz laser radiation, obtained in the first experiments, are also presented in the paper. У Сибірському центрі фотохімічних досліджень навесні 2003 року отримана генерація випромінювання з довжиною хвилі 140 мкм на потужному лазері на вільних електронах (ЛВЕ). У роботі коротко описана конструкція ЛВЕ на базі прискорювача рекуператора і представлені результати вимірювання деяких параметрів електронного пучка і терагерцового випромінювання. В Сибирском центре фотохимических исследований весной 2003 года получена генерация излучения с длиной волны 140 мкм на мощном лазере на свободных электронах (ЛСЭ). В работе кратко описана конструкция ЛСЭ на базе ускорителя рекуператора и представлены результаты измерения некоторых параметров электронного пучка и терагерцового излучения.